An adaptive nonlinear observer for sensorless wind energy conversion system with PMSG. (May 2020) - Watil, Aziz; El Magri, Abdelmounime; Raihani, Abdelhadi; Lajouad, Rachid; Giri, Fouad
Abstract: This paper addresses the problem of designing an adaptive nonlinear observer for wind energy conversion systems (WECSs). The study targets specifically a synchronous aero-generator connected to the grid using AC/DC/AC converter. The main objective of the present work is to establish a different approach for estimating the rotor speed, position and the turbine torque. Furthermore, the proposed technique aims to provide measures of the grid voltage, considered generally as accessible. Indeed, the considered voltage values in general are supposed to be the same as given by the transformer. However, transformers are generally positioned at long distances from measuring points. Unlike previous studies, the grid frequency is considered as an unknown parameter and time varying. Thus, electrical currents are the only needed measures. This proposed strategy, considered as sensorless, is validated by a formal analysis proving that all objectives are achieved. Finally, several simulations have conclusively proven that the proposed observer enjoys additional high robustness qualities.